Clinico-pathological features of Newcastle disease in Japanese quails (Coturnix Cotunix Japonica) infected with Newcastle disease virus AF2240 strain - Nur Atikah Hashim
Various birds are susceptible to Newcastle disease viruses (NDV). This has become a concern to poultry industry as quails might become a potential carrier in disease outbreak as reported in some studies. This experiment was conducted to determine the susceptibility of Japanese quails (Coturnic cortunix japonica) towards Newcastle disease virus (NDV) Ad2240 strain. The AF2240 strain is a Malaysian viscerotropic strain that was isolated during an outbreak in the country in the 1960s. The induction of NDV of this strain is expected to determine the susceptibility of the local domesticated quails towards NDV AS2240 strain. 24 quails of 2 weeks of age were randomly selected and equally divided into four groups. The first three groups (Group A, B, and C) were administered with three different doses of antigen (EID50 7.3log10/0.1ml) (respectively (0.1ml, 0.1ml, 0.3ml) intramuscularly with a negative control group. On day six of post infection, clinical changes including ruffled feathers, depression, incoordination, lameness, anorexia, diarrhea, recumbent and paralysis of wings and legs were significantly observed in some of the infected quails in each groups. Clinical signs of all quails significantly shown (p<0.05) starting from day 6 to day 9 of post challenge. However, there were no significant differences (p<0.05) between the three infected groups. Based on serological examination using ELISA, all quails in each group did not show increase in antibody titre during experimental period. Significant lesions were observed upon postmortem examination of infected quails of all groups including congestion and haemorrhages of intestine, congestion of liver, brain, pectoral muscles, heart and lungs. The pathological lesions significantly increased (p<0.05) throughout the study. There were significant difference (p<0.05) between control and infected group. However there were no significant difference (p<0.05) between the three treatment groups. In conclusion, Japanese quails are susceptible towards Newcastle Disease Virus AFF2240 which may cause severe clinical impacts and even lead to fatality. However, this study also suggesting that highest dose of virus does not necessarily causing most severe clinic-pathological effects or highest antibody titre.